Evaluating the Effects of 1-Methylcyclopropene Concentration and Immersion Duration on Ripening and Quality of Banana Fruit - Rahman, M A; Hossain, M A; Begum, M M; Banu, S P; Arfin, M S (Journal of Postharvest Technology, 2014)
The influence of different concentrations of aqueous 1-methylcyclopropene (1-MCP) in delaying the ripening process of harvested banana fruit (Musa sp., AAA group, cv. BARI Kola-1) was investigated. Banana fruits at mature green stage were immersed in aqueous 1-MCP at 100, 300 and 500 μg L-1 for 5, 10 and 15 min, fan-forced air-dried and kept into 1% perforated low density polyethylene bag. The fruits were then stored at 20±2 °C and 75-80% RH for ripening over 35 days. Banana ripening was delayed when immersed in 100-500 μg L-1 1-MCP solution however; higher concentrations were more effective. The efficacy of 1-MCP was not significantly influenced by immersion durations of 5, 10 and 15 min. The changes in respiration rate, fruit firmness, TSS, ascorbic acid contents and surface colour of bananas subjected to all three concentrations of 1-MCP remained strongly suppressed and consequently extended the storage life by 15 days compared to untreated fruit. Increased storage life of banana occurred without affecting the peel appearance, pulp texture, soluble solids concentration and aroma profiles. Nevertheless, crown rot disease initiated at the later stage of ripening although individual finger was not affected until end of the storage. Thus, postharvest immersion of banana fruit in aqueous 1-MCP at 100 μg L-1 solution for 5 min could extend the storage life up to 35 days without compromising fruit quality and could be a feasible alternative technology for long distance transportation and marketing.
Keywords: Banana; Ripening change; 1-MCP; Respiration; Firmness; Storage life